Cultural Ecosystem Services in urban areas peripheral to the Petrochemical Complex El Tablazo-Venezuela - Quintero-Sandrea, Carolina (Estoa. Journal of the Faculty of Architecture and Urbanism, 2026)
Cultural ecosystem services (CES) value the intangible benefits that ecosystems provide to people and are useful tools for urban planning and management. This study aims to identify CES in urban areas peripheral to the El Tablazo Petrochemical Complex, Venezuela. Based on the review of urban plans, questionnaires to experts and participatory mapping with focus groups, the main ecosystems and their benefits are identified. The marshes and the Altagracia coast (Lake Maracaibo) stand out as key ecosystems, together with the system of green public spaces (streets, squares, waterfront promenade), providing recreational, physical and emotional benefits. These spaces, despite the tension with petrochemical activity, are essential for the articulation of the city, contributing to the quality of life and well-being of its inhabitants.